Undang-Undang Sistem Peradilan Anak, Pelajaran dari Kearifan Lokal dan Kasus Raju - Ferry Fathurokhman (Universitas Syiah Kuala, 2013)
ABSTRACT: Prior to colonization of Dutch, most of Indonesian solve legal problem by making an agreement. A court is a modern legal representation for Indonesian that is the last way taken if fail to reach an agreement. The settling of criminal case through a court is often leaving social problem. The enforcement of juvenile case is a dominant problem that can be seen. Raju case and AAL are juvenile cases causing social tension. In the context of modern law, a crime is a crime, law must be enforced. Despite the fact that most Indonesian believe that two cases are insignificant for being tried before the court that may bring negative impact on the future of the children. A new regime law, the Law of Juvenile Justice System has been passed. A new hope for settling the cases. The Act of Juvenile Justice System, A Lesson from Local Wisdom and Raju Case